2017
DOI: 10.1002/jssc.201601155
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis fingerprints combined with chemometric methods to evaluate the quality consistency and predict the antioxidant activity of Yinqiaojiedu tablet

Abstract: The quality consistency of Yinqiaojiedu tablets (YQJDTs) was monitored by extracting their electrophoretic fingerprint and marker compound data that were obtained using capillary electrophoresis. To select the suitable background electrolyte, wing-shape method was proposed. A background electrolyte composed of 103.1 mM boric acid, 51.6 mM sodium borate, 9.8 mM disodium hydrogen phosphate, and 15.6 mM sodium dihydrogen phosphate was used to separate compounds. Under the optimized conditions, the content of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…CE has been used for fingerprint analyses of various raw materials and products containing medicinal plants such as Ginkgo biloba ( Johnson and Lunte, 2016 ), Smilax glabra Roxb. ( Zhang and Cheung, 2011 ), Carthamus tinctorius L.( Sun et al, 2003 ), Scutellaria baicalensis ( Yu et al, 2007 ; Wang Y. et al, 2014 ), Dendrobium candidum ( Zha et al, 2009 ), Glycyrrhiza uralensis ( Ma et al, 2017 ; Gong et al, 2021 ), etc. Gong et al recently reported a quality evaluation of Compound Liquorice Tablets (a Western-Chinese herbal preparation containing liquorice extract, powdered poppy, camphor, star anise oil, and sodium benzoate) using CE with UV detection ( Gong et al, 2021 ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…CE has been used for fingerprint analyses of various raw materials and products containing medicinal plants such as Ginkgo biloba ( Johnson and Lunte, 2016 ), Smilax glabra Roxb. ( Zhang and Cheung, 2011 ), Carthamus tinctorius L.( Sun et al, 2003 ), Scutellaria baicalensis ( Yu et al, 2007 ; Wang Y. et al, 2014 ), Dendrobium candidum ( Zha et al, 2009 ), Glycyrrhiza uralensis ( Ma et al, 2017 ; Gong et al, 2021 ), etc. Gong et al recently reported a quality evaluation of Compound Liquorice Tablets (a Western-Chinese herbal preparation containing liquorice extract, powdered poppy, camphor, star anise oil, and sodium benzoate) using CE with UV detection ( Gong et al, 2021 ).…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…rhamnosyl kaempfero 20 mM phosphate 5 mM β-cyclodextrin (β-CD), 40 [103] nd-no data, LOQ-limit of quantification,…”
Section: Field Of Applicationmentioning
confidence: 99%
“…The 25 samples from two manufacturers were clearly divided into two clusters based on the principal component analysis. In fingerprint assessments, systematic quantified fingerprint method was used for integrative quality discrimination of YQJDTs from both qualitative and quantitative perspectives, by which the qualities of 25 samples were well differentiated .…”
Section: Applicationsmentioning
confidence: 99%